PENYULUHAN , SIKAT GIGI MASAL, DAN PENGOBATAN PENYAKIT GIGI DAN MULUT DALAM PENINGKATAN KESEHATAN GIGI DAN MULUT DI NAGARI AIE DINGIN, KABUPATEN SOLOK - Nila Kusuma; Fildzah Nurul Fajrin (Jurnal Pengabdian Warta Andalas, 2018)
Dental and oral health is an important part of health body since mouth is the vulnerable port de entre ofdisease . Therefore, oral health should always be maintained. Healthy teeth results in comfort in talking,eating, drinking,and doing all primary activities that humans desperately need. Therefore, communityservice activities to improve and care for dental and oral health at the national level. Through thisdedication is expected dentists can share knowledge to the community as a form of community service. Theservice activities are held in Nagari Aie Dingin, Solok consist of counseling, mass toothbrushing , anddental treatment.